Global partnerships on paper and in practice: Critical observations from inside a Global Challenge Research Fund capacity‐development project. (16th March 2022) - Axelby, Richard; Worku‐Dix, Bethel; Crewe, Emma
Abstract: This article describes the bureaucratic processes required to establish and manage a single international capacity‐development project that brought together a funding council (AHRC), UK University (SOAS University of London) and universities and other research organisations in Myanmar and Ethiopia. Drawing from ethnographic critiques of the planning and audit practices employed in international development and in the UK University sector, we track the formal certification of partnership as enacted through due diligence and contracts, budgets and timeframes, and reconciliations and reporting. These practices point to pervasive assumptions about capacity transfer and the unequal basis of international research coalitions spanning the Global North and Global South. In this article, we challenge these assumptions by documenting how the allocation of capacity is constrained in hierarchies of time and space. For equitable partnership arrangements to be achieved, we recommend that capacity development be considered a long‐term exchange that flows from mutual reflection and learning from one another.